Mexican ballads, Chicano poems : history and influence in Mexican-American social poetry - Limón, José Eduardo (New historicism ;, 1992)
Mexican Ballads, Chicano Poems combines literary theory with the personal engagement of a prominent Chicano scholar. Recalling his experiences as a student in Texas, José Limón examines the politically motivated Chicano poetry of the 60s and 70s. He bases his analyses on Harold Bloom's theories of literary influence but takes Bloom into the socio-political realm. Limón shows how Chicano poetry is nourished by the oral tradition of the Mexican corrido, or master ballad, which was a vital part of artistic and political life along the Mexican-U.S. border from 1890 to 1930.Limón's use of Bloom, as well as of Marxist critics Raymond Williams and Fredric Jameson, brings Chicano literature into the arena of contemporary literary theory. By focusing on an important but little-studied poetic tradition, his book challenges our ideas of the American canon and extends the reach of Hispanists and folklorists as well.